40 from Israel : Contemporary Sculpture & Drawing. - Brooklyn Museum, New York; Bass Museum Miami Beach, Florida; Museum of Modern Art Mexico City; Jewish Museum Amsterdam (New York : The Brooklyn Museum, 1988)
Averbuch, Ilan ; Ben-David, Zadok ; Ben Haim, Zigi ; Ben Zvi, Roni ; Berman, Reuven ; Borkovsky, Joshua ; Cohen Gan, Pinchas ; Dorchin, Yaakov ; Dominey, Drora ; Eshet, Pinchas ; Feldman, Dorit ; Fine, David ; Gechtman, Gideon ; Eshel Gershuni, Bianka ; Gejer, Teresa ; Gross, Michael ; Hadany, Israel ; Hefetz, Yaakov ; Hecker, Zvi ; Heimann, Shoshana ; etc.
40 from Israel : Contemporary Sculpture & Drawing, Brooklyn Museum, New York, April 18 - June 27, 1988 / Bass Museum Miami Beach, Florida, 22 July - 25 September, 1988 / Museum of Modern Art Mexico City, 25 October - 8 December 1988 / Jewish Museum Amsterdam, 23 February - 8 April, 1989
boek